2005
DOI: 10.1042/bj20050709
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the molecular bases ofMycobacterium tuberculosisbinding to the lectin DC-SIGN reveals an underestimated complexity

Abstract: Interactions between dendritic cells and Mycobacterium tuberculosis, the aetiological agent of tuberculosis in humans, are thought to be central to anti-mycobacterial immunity. We have previously shown that M. tuberculosis binds to human monocyte-derived dendritic cells mostly through the C-type lectin DC-SIGN (dendritic-cell-specific intercellular molecule-3-grabbing non-integrin)/CD209, and we have suggested that DC-SIGN may discriminate between mycobacterial species through recognition of the mannose-cappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 46 publications
6
125
0
Order By: Relevance
“…Nevertheless, the potential importance of DC-SIGN ligation during infection is illustrated by the large number of DC-SIGN ligands that (pathogenic) mycobacteria may express. Together with ManLAM (39), lipomannan (72), mannose-capped arabinomannan (72), two mannosylated glycoproteins (72), and the phosphatidylinositol mannosides (73), ␣-glucan represents the seventh documented mycobacterial ligand for DC-SIGN. Interestingly, it has been shown that in patients with TB up to 70% of alveolar macrophages show DC-SIGN expression (71).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the potential importance of DC-SIGN ligation during infection is illustrated by the large number of DC-SIGN ligands that (pathogenic) mycobacteria may express. Together with ManLAM (39), lipomannan (72), mannose-capped arabinomannan (72), two mannosylated glycoproteins (72), and the phosphatidylinositol mannosides (73), ␣-glucan represents the seventh documented mycobacterial ligand for DC-SIGN. Interestingly, it has been shown that in patients with TB up to 70% of alveolar macrophages show DC-SIGN expression (71).…”
Section: Discussionmentioning
confidence: 99%
“…We recently described Mtb manno-proteins as an emerging class of bacterial adhesins that contribute to Mtb infectiousness through binding to host innate-immune system receptors, including lung surfactant protein A (SP-A) (1) and DC-SIGN (2), which are considered to be the receptors preferentially used by mycobacteria to enter target cells and evade host defense mechanisms (3). Here, we considered the systemic impact of protein mannosylation on the survival and virulence of Mtb.…”
mentioning
confidence: 99%
“…Several ligands have been studied so far: the mannosylated 19-kDa and 45-kDa antigens, mannose-capped lipoarabinomannan (ManLAM), arabinomannan (AM), lipomannan (LM), and phosphatidylinositol mannosides (PIMs) (27,46,59,67). The 19-and 45-kDa glycoproteins were shown to have an inhibitory effect on mycobacterial binding to DC-SIGN (59). However, M. tuberculosis mutants deficient in these glycoproteins bound DC-SIGN as well as the wild-type strain did (59).…”
mentioning
confidence: 99%